PENGARUH BRAND IMAGE, KUALITAS PRODUK DAN PROMOSI PENJUALAN TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR HONDA PADA PT CAPELLA DINAMIK NUSANTARA - Wendelin Franke Wong; Viviana vivi; Nurlince Fransiska Simanjuntak; Felix lix (Jurnal Ekonomi Bisnis Manajemen Prima, 2022)
The purpose of this study analyze the effect of Brand Image, Product Quality, and Sales Promotion on Purchase Decisions for Honda Motorcycles at PT Capella Dinamik Nusantara. This research uses quantitative descriptive research and the sampling technique in this study uses the slovin formula with a total of 70 respondents. Primary data in this study were taken by means of interviews and distributing questionnaires. The data processing technique used is descriptive analysis method and multiple linear regression analysis, classical assumption test, instrument test (validity and reliability), hypothesis testing, and coefficient of determination using SPSS for Windows program. The results of this study indicate that simultaneously brand image, product quality and promotion have a positive and significant effect on purchasing decisions for motorcycles at PT Capella Dinamik Nusantara. Promotion is the most dominant variable influencing motorcycle purchasing decisions at PT Capella Dinamik Nusantara. Adjusted R Square value of 0.253 which means 25.3% of purchasing decisions can be explained by variations of the three independent variables (brand image, product quality and promotion) while the remaining 74.7% is influenced by other variables not discussed in this study.